Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1055/a-1120-8428
|View full text |Cite
|
Sign up to set email alerts
|

Slow-pull compared to suction technique for EUS-guided sampling of pancreatic solid lesions: a meta-analysis of randomized controlled trials

Abstract: Background and study aims Current ESGE guidelines suggest employing the suction (SU) technique for endoscopic ultrasound (EUS)-guided sampling of pancreatic solid lesions. Nonetheless, recent randomized controlled trials (RCT) have reported that the slow-pull (SP) technique has similar diagnostic accuracy with possibly less blood contamination. However, these results are heterogeneous and limited to small cohorts. The aim of this meta-analysis was to compare adequacy, accuracy, sensitivity and specificity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…In a retrospective study of 97 cases of EUS-FNA that were performed with either the slow pull technique or conventional suction, the slow pull technique reduced cellularity and blood contamination when a 25-gauge FNA needle was used, but not when a 22-gauge needle was used, resulting in higher diagnostic sensitivity [18]. The current meta-analysis reveals that the slow pull technique was not superior to conventional suction, although it resulted in reduced blood contamination [19].…”
Section: (4) Slow Pullmentioning
confidence: 74%
“…In a retrospective study of 97 cases of EUS-FNA that were performed with either the slow pull technique or conventional suction, the slow pull technique reduced cellularity and blood contamination when a 25-gauge FNA needle was used, but not when a 22-gauge needle was used, resulting in higher diagnostic sensitivity [18]. The current meta-analysis reveals that the slow pull technique was not superior to conventional suction, although it resulted in reduced blood contamination [19].…”
Section: (4) Slow Pullmentioning
confidence: 74%
“…However, a recent meta-analysis of randomized trials concluded nonsuperiority of one approach over the another. [ 22 ] In addition, our study was not adequately powered to assess the difference in the diagnostic yield among different types or sizes of needles.…”
Section: Discussionmentioning
confidence: 99%
“…The fanning technique was used in all passes, according to ESGE guidelines 11 . Since the “slow-pull technique” applies some negative pressure in the needle (5 % of the force generated with the syringe) 12 13 in the cases without suction (S–) the stylet was not used during the FNB puncture.…”
Section: Methodsmentioning
confidence: 99%